2012
DOI: 10.1590/s0103-21002012000300023
|View full text |Cite
|
Sign up to set email alerts
|

A rede de relações e interações da equipe de saúde na atenção básica e implicações para a enfermagem

Abstract: Objective: To characterize the networks of relationships and interactions in the healthcare team in primary care, and its implications for nursing. Method: An integrative review of literature for the identification of papers about networks of relationships and interactions between members of the healthcare team in primary care and its implications for nursing, published during the period between January 2001 and July 2008. The search occurred using the databases of the Virtual Health Library and SCOPUS, contem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
12

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
(30 reference statements)
0
4
0
12
Order By: Relevance
“…The lack of partnerships with institutions in the community was related to fewer FNA for adults and families. This may be because the health sector does not respond to the health needs of the population in isolation and thus there is a need to articulate health actions with other sectors of society, to strengthen and qualify health care 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…The lack of partnerships with institutions in the community was related to fewer FNA for adults and families. This may be because the health sector does not respond to the health needs of the population in isolation and thus there is a need to articulate health actions with other sectors of society, to strengthen and qualify health care 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…1,2,5 The results also indicated the presence of conflicts between professionals within the primary health care context. This demonstrates that human relations are one of the biggest challenges of teamwork, where the individual behavior of each member ends up becoming the main barrier to the team integration 26 and the development of interdisciplinarity. In terms of the potential for health education selforganization, the results indicated that health professionals can promote improvements in the care of people with DM in PHC, primarily through groups with different methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…22 Pues, frente a los aspectos contrarios, un trabajador, valiéndose de su poder jerárquico, puede asediar moralmente a otro miembro del equipo, como en situaciones en que los jefes asumen posturas autoritarias y arrogantes en los contactos interpersonales. 23 La perspectiva mencionada necesita ser reflexionada en y con el equipo de enfermería, que está compuesto por diferentes cargos tanto en la realidad brasileña, como en la española. En la institución estudiada existen: enfermeros, con formación superior, subdivididos en enfermeros supervisores responsables de los equipos de enfermería de los diversos sectores del hospital y enfermeros de cabecera; también, auxiliares con formación mediante cursos de capacitación, estando bajo la supervisión del enfermero de cabecera.…”
Section: (E4)unclassified